Baskets of plants and animals: conservation of organic archaeological macro-remains - Medeiros da Silva, Francini (2020)
The increasing number of archaeobotanical and zooarchaeological research projects has shown the importance of these sub-disciplines to research on human occupation in Brazil, primarily relating to how populations used, managed, and domesticated plants and animals over time. However, publications about the conservation of these remains, that are specific due to their organic nature and the action of different processes of degradation, have not accompanied this research. To this end, this article seeks to present practices employed in different archaeological contexts for the conservation of botanical and faunal macro-remains, from their recovery in the field to their preparation for definitive storage in collection archives.